Manajemen Pembelajaran Guru SMP Karya Bunda Mandiri Kec. Percut Sei Tuan KAB. Deli Serdang - Nurdalila; Rohman, Fatkhur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to describe the management of teacher learning at Karya Bunda Mandiri Middle School, kec. Precut Sei Tuan, Kab. Deli Serdang. This study uses a description method with qualitative data analysis. This method aims to intensively study the background of the current situation and the environmental interactions of a social unit, be it individuals, groups, institutions or society. A descriptive research with a qualitative approach was carried out by digging up data sourced from the location. Data collection was collected through a qualitative analysis approach, by means of interviews, observation, and documentation. This research was conducted at Karya Bunda Mandiri Middle School, Kec. Percut Sei Tuan, Kab. Deli Serdang. The subject of this research is the teacher. This research is collaborative between researchers and teachers. The results of this study indicate that in the learning process, of course there is learning management under the teacher.